Functional Supramolecular Gels Based on the Hierarchical Assembly of Porphyrins and Phthalocyanines - Feng, Xuenan; Liu, Chenxi; Wang, Xiqian; Jiang, Yuying; Yang, Gengxiang; Wang, Rong; Zheng, Kaishun; Zhang, Weixiao; Wang, Tianyu; Jiang, Jianzhuang (Frontiers in Chemistry, 2019)
Supramolecular gels containing porphyrins and phthalocyanines motifs are attracting increased interests in a wide range of research areas. Based on the supramolecular gels systems, porphyrin or phthalocyanines can form assemblies with plentiful nanostructures, dynamic and stimuli-responsive properties. And these π-conjugated molecular building blocks also afford supramolecular gels with many new features, depending on their photochemical and electrochemical characteristics. As one of the most characteristic models, the supramolecular chirality of these soft matters was investigated. Notably, the application of supramolecular gels containing porphyrins and phthalocyanines has been developed in the field of catalysis, molecular sensing, biological imaging, drug delivery and photodynamic therapy. And some photoelectric devices were also fabricated depending on the gelation of porphyrins or phthalocyanines. This paper presents an overview of the progress achieved in this issue along with some perspectives for further advances.